Does the Hispanic Mortality Advantage Vary by Marital Status Among Postmenopausal Women in the Women's Health Initiative?. Issue 7 (15th January 2021) - Flores, Melissa; Ruiz, John M; Butler, Emily A; Sbarra, David A; Garcia, David O; Kohler, Lindsay; Crane, Tracy E; Corbie-Smith, Giselle; Benavente, Viola; Kroenke, Candyce H; Saquib, Nazmus; Thomson, Cynthia A
Abstract: Background: Literature assessing the effect of marital status on mortality has underrepresented, or altogether omitted Hispanics and the potential moderating effect of Hispanic ethnicity on these relationships. Given cultural and network dynamics, marital advantages in older Hispanic women may be greater than other groups given their family-focused, collectivist orientation. Purpose: The purpose of this study was to understand whether older Hispanic women exhibited a more pronounced marital advantage as compared with non-Hispanic Whites. Methods: We used longitudinal data from the Women's Health Initiative (WHI) Observational Study and Clinical Trials ( N = 161, 808) collected initially from 1993 to 1998 and followed until 2018. Our sample excluded those respondents indicating "other" as their race-ethnicity and those missing marital status and race-ethnicity variables ( N = 158, 814). We used Cox-proportional hazards models to assess the association between race-ethnicity, marital status, and the interactive effect of race-ethnicity and marital status on survival. Results: After controlling for socioeconomic status (SES) and health controls, we found a Hispanic survival advantage when compared with non-Hispanic Whites and all other racial-ethnic groups with the exception of Asian/Pacific Islander women (all significant HRs < 0.78, all p s ≤ 0.001). Hispanics had a higher rate of divorce when compared with non-Hispanic Whites. The interactive effect of race-ethnicity and marital status was not significant. Conclusions: U.S. Hispanic, postmenopausal women exhibit a mortality advantage over and above marital status despite their high rates of divorce. Implications and potential explanations are discussed. Clinical Trial Registration: NCT00000611. Abstract : The density of Hispanic residents in a neighborhood may be protective for 5-year, depressive symptoms, and cardiovascular events for both older adults of Hispanic/Latino(x) ethnicity and other racial-ethnic groups.